Potential for cleaner energy recovery and electricity generation from abattoir wastes in Nigeria - E. L. Odekanle; O. J. Odejobi; S. O. Dahunsi; F. A. Akeredolu (Energy Reports, 2020)
Energy recovery and electricity generation from abattoir wastes was investigated with the aim of combating both energy crises and environmental pollution problems. Anaerobic digestion was carried out in a two 10 L batch digesters for about 30 days under mesophilic condition. Biogas volume was measured by water displacement method at every 24h interval. Based on the volume of biogas produced and its methane composition, electricity value of the produced biogas was estimated. Daily average and cumulative gas volumes of 0.00103 m3/kg VS (1.03 liters) and 0.0309 m3/kg VS (30.90 liters) were obtained respectively with 63.4% methane composition. The results suggest that 1040 MWh and 1664.6 MWh of electricity can be generated from biogas at low-end conversion efficiency of 25% and at high-end high-end conversion efficiency respectively. The study concluded that waste to wealth technology, if appropriately explored is a viable solution to energy crises in Nigeria.
Keywords: 330; Energy; Abattoir; Biogas; Electricity; Fossil fuel